Afet çalışanlarında psikolojik dayanıklılık ve stresle başa çıkma düzeyi - ÇOBAN, Hafize (My University, 2020)
This research was carried out to examine the ways of disaster employees working in disasters to deal with psychological resilience and stress and to attract attention. For this purpose, medical and search and rescue teams working in Istanbul, which had to intervene in emergency and disaster situations that are dense in terms of population and region, were preferred. Descriptive and cross-sectional research was carried out with the Disaster and Emergency Management Directorate, 112 Provincial Ambulance Service, and National Medical Rescue Team employees working on the European side of Istanbul between February 2019 - May 2019. The data were collected in the light of expert opinions and literature, using the Introductory Information Form, Psychological Resilience Scale and Stress Coping Scale forms. In the analysis of the data obtained in this study IBM SPSS Statistics 22 (IBM SPSS, Turkey) programs were used. Significance value was taken as p <0.05. The correlation coefficient between Stress Coping variable and Psychological Resilience used in the study was calculated to be statistically significant at the significance level of 0.05, which was calculated as 0.584. A moderate relationship was detected between these two variables in the same direction. 228 people participated in the study carried out in two different institutions in Istanbul province and consists of 114 female and 114 male personnel. According to the demographic information, when looking at the psychological resilience levels, the ratio of 114 females was 81.11%, while 114 males were 81.63%. The marital status was found as 81.08%, with the single rate of 113, and the rate of 115 people with the rate of 81.66%. It was determined that it constitutes 82.64% and 28-36 years old personnel in the age variable. According to the educational level, the highest value was graduate staff with 84.12%. When we look at the gender variable with the levels of coping with stress, the ratio of 114 males was 89.29%, and the proportion of 114 females was 87.77%. Even though the rates are close, the level of male employees is high. According to the age variable, the highest value was found in personnel between the ages of 37-45 with a rate of 92%. In marital status, the proportion of 115 married people increased 90.20%, and there was no statistically significant value among singles. In educational situations, 51 people with a bachelor's degree were higher with 90.86%. According to the psychological resilience scale, disaster workers got the highest score from the challenge sub-dimension and the lowest score from the control sub-dimension. According to the stress coping scale, the most effective method consists of problem-oriented approaches. When the responses were evaluated, the problem solving dimension got the highest score, and it was found that the employees made individual behavioral interventions and the support seeking scores were low accordingly. This reveals the importance of social support. Although the level of psychological resilience and stress coping of disaster workers is high, group studies should be done in order to ensure that the staff socialize and see the social support of their environment.
Bu araştırma afetlerde görev alan afet çalışanlarının psikolojik dayanıklılık ve stresle başa çıkma yollarını incelemek ve dikkat çekmek amacıyla yapılmıştır. Bu amaçla nüfus ve bölge açısından yoğun olan acil ve afet durumlarına sık sık müdahale etmek zorunda kalan özellikle İstanbul'da görev yapan medikal ve arama-kurtarma ekipleri tercih edilmiştir. Tanımlayıcı ve kesitsel araştırma Şubat 2019 - Mayıs 2019 tarihlerinde İstanbul Avrupa yakasında görev alan Afet ve Acil Durum Yönetimi Başkanlığı, 112 İl Ambulans Servisi, ve Ulusal Medikal Kurtarma Ekipleri çalışanları ile yapıldı. Veriler uzman görüşleri ve literatür ışığında Tanıtıcı Bilgi Formu, Psikolojik Dayanıklılık Ölçeği ve Stresle Başa Çıkma Ölçeği formları ile toplanmıştır. Çalışmada elde edilen bulguların analizinde IBM SPSS Statistics 22 (IBM SPSS, Türkiye) programı kullanılmıştır. Anlamlılık değeri p<0,05 alınmıştır. Araştırmada kullanılan Stresle Başa Çıkma değişkeni ile Psikolojik Dayanıklılık arasındaki korelasyon katsayısı 0,584 olarak hesaplanmış 0,05 olan anlamlılık düzeyinde istatistiksel olarak anlamlı olduğuna karar verilmiştir. Bu iki değişken arasında aynı yönde orta derecede ilişki tespit edildi. İstanbul ilinde iki farklı kurumda yapılan çalışmaya 228 kişi katılım sağlamış olup 114 kadın ve 114 erkek personelden oluşmaktadır. Demografik özelliklere göre psikolojik dayanıklılık düzeylerine bakıldığında cinsiyet olarak 114'ü kadın oranı % 81,11 bulunurken, 114 erkek ise % 81,63 bulundu. Medeni durumları 113 kişi bekar oranı % 81,08 olarak 115 kişi evli oranı ise % 81,66 olarak bulundu. Yaş değişkeninde % 82,64 ile 28-36 yaş arası personel oluşturduğu saptandı. Eğitim durumuna göre ise en yüksek değer %84,12 ile lisansüstü personel oluşturdu. Stresle başa çıkma düzeyleri ile cinsiyet değişkenine baktığımızda 114 erkek oranı % 89,29, 114 kadın oranı %87,77 olarak çıktı. Oranlar yakın olsa da erkek çalışanların düzeyi yüksek çıktı. Yaş değişkenine göre en fazla değer % 92 oranla 37-45 yaş arası personelde bulundu. Medeni durumlarında ise evli 115 kişinin oranı % 90,20 çıkarak bekarlar arasında istatistiksel olarak anlamlı bir değer çıkmadı. Eğitim durumlarında, lisans mezunu 51 kişi % 90,86 ile yüksek çıktı.Yapılan psikolojik dayanıklılık ölçeğine göre afet çalışanları en yüksek puanı meydan okuma alt boyutundan, en düşük puanı ise kontrol alt boyutundan almıştır. Stresle başa çıkma ölçeğine göre en etkili yöntem sorun odaklı yaklaşımlardan oluşmaktadır. Yanıtlar değerlendirildiğinde problem çözme boyutu en yüksek puanı almış ve çalışanların bireysel davranışsal girişimlerde bulunduğu ve destek arama puanlarının da bununla uyumlu olarak düşük çıktığı tespit edilmiştir. Bu da sosyal desteğin önemini ortaya çıkarmaktadır.Afet çalışanlarının psikolojik dayanıklılık ve stresle başa çıkma düzeyleri yüksek olmakla beraber genel olarak bireysel çözüm yöntemleri kullandıkları, personelin sosyalleşmesi ve çevresinin de sosyal desteğini görebilmesi için grup çalışmaları yapılmalıdır.
Keywords: Afet Yönetimi Anabilim Dalı; Afet Yönetimi; Afetler = Disasters; Department of Disaster Management; AFAD; Stress; 112; UMKE; Disaster and Emergency Management Authority (AFAD)